Determinants of neonatal jaundice among neonates admitted to five referral hospitals in Amhara region, Northern Ethiopia: an unmatched case-control study - Birhan Alemnew; Addisu Getie; Adam Wondmieneh; Getnet Gedefaw; Asmamaw Demis Bizuneh (BMJ Publishing Group, 2020)
Background Neonatal jaundice is associated with a significant risk of neonatal morbidity and mortality. It is a major cause of hospital neonatal intensive care unit admission and readmissions during the neonatal period. Hence, the study aimed to identify the determinant factors of neonatal jaundice among neonates admitted at five referral hospitals in Amhara region, Northern Ethiopia.Method A hospital-based unmatched case-control study design was employed, on 447 neonates (149 cases and 298 controls) at referral hospitals in Amhara region, Northern Ethiopia, from 1 March to 30 July 2019. Consecutive sampling method was used to select both the cases and controls. The collected data were entered into Epi data V.4.2 and then exported into SPSS window V.24 for analysis. Bivariable and multivariable analysis were carried out by using binary logistic regression. A p value of <0.05 was considered as significant difference between cases and controls for the exposure variable of interest.Results The median (±IQR) age of neonate at the time of admission and gestational age were 3±2 days and 38 (±3) weeks, respectively. Prolonged duration of labour (adjusted OR (AOR)=2.45, 95% CI 1.34 to 4.47), being male sex (AOR=3.54, 95% CI 1.99 to 6.29), low birth weight (AOR=5.06, 95% CI 2.61 to 9.82), birth asphyxia (AOR=2.88, 95% CI 1.38 to 5.99), sepsis (AOR=2.49, 95% CI 1.22 to 5.11) and hypothermia (AOR=2.88, 95% CI 2.63 to 14.02) were the determinant factors for neonatal jaundice.Conclusions Prolonged duration of labour, hypothermia, sepsis, birth asphyxia, low birth weight and sex of neonate were independent determinants of neonatal jaundice. Early recognition and management of identified modifiable determinants are the recommended interventions.